La estrategia del Scottish National Party: ¿la independencia al servicio de la reforma constitucional? (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2012)
Despite winning the Scottish elections (2011) with a pro-independence slogan, the SNP has been forced to change his aim. The fact that only 20% of Scots are supporters of the break with United Kingdom has motivated Alex Salmond to delay the date of holding the referendum in which he tries to introduce additional questions, with the opposition from David Cameron, in order to achieve more political powers for the Parliament in Edinburgh.The Unionist Parties (Conservatives, Liberals and Labour) are supporters of a constitutional reform which aim is to strengthen the Union, never set the bases for an immediate and subsequent dismemberment of its Member Nations.
Keywords: Independence; referendum; sovereignty; Salmond; David Cameron; Ed Miliband; Nationalism; Scotland Act Unión